1990
DOI: 10.1177/0310057x9001800417
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxaemia during Postoperative Recovery using Continuous Pulse Oximetry

Abstract: Continuous pulse oximetry monitoring was used to determine the incidence of hypoxaemia (arterial oxygen saturation ≤ 90%) occurring in the first hour of postoperative recovery. Of 107 patients studied, hypoxaemia was recorded in 80%. Twenty-eight (26%) of these patients had saturations below 80%. The average frequency (i.e., the number of desaturations per patient) and the total duration of these desaturations was 7.7 desaturations and 182 seconds respectively. Intermittent measurements taken preoperatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Earlier work showed that pulse oximeters failed in the operating room in 2.5% of 10,312 patients randomized to be monitored [8]. Pulse oximeter failure rates are even higher in critical care, intensive care, and Postanesthesia Care Unit (PACU) environments [9]. New-generation pulse oximeters are designed to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work showed that pulse oximeters failed in the operating room in 2.5% of 10,312 patients randomized to be monitored [8]. Pulse oximeter failure rates are even higher in critical care, intensive care, and Postanesthesia Care Unit (PACU) environments [9]. New-generation pulse oximeters are designed to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has important clinical consequences, as sub-anaesthetic concentrations are present after operation when patients are relatively unsupervised. Suppression of the hypoxic ventilatory response would therefore be hazardous in patients after operation, as large clinical studies have reported frequent hypoxaemia in recovery room patients [7,8].…”
mentioning
confidence: 99%
“…Morbidly obese patients are at increased risk for complications from general anesthesia and surgery [1][2][3][4][5][6]. In comparing desflurane with sevoflurane in morbidly obese patients undergoing laparoscopic gastroplasty, recovery characteristics between the two agents were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these risks include difficult tracheal intubation, aspiration, airway obstruction, atelectasis, decreased functional residual capacity, increased airway resistance, oxygen desaturation, and sleep apnea syndrome, which can further complicate postoperative respiratory recovery [1][2][3][4][5][6]. Even slight improvement in early or intermediate airway recovery would be beneficial because obese patients would be more apt to maintain higher oxygen saturation (Spo 2 ) after surgery and less likely to have cardiac and respiratory complications in the postoperative period.…”
Section: Introductionmentioning
confidence: 99%